Internal hydrocephalus caused by Coenurus cerebralis in a ewe (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: Coenurosis is a parasitic disease that particularly affects sheep and goats. The disease is caused by Coenurus cerebralis which is the larval stage of Taenia multiceps. The objective of this study was to investigate the clinical and the pathological lesions caused by C. cerebralis in a ewe.Materials and methods: Two-and-a-half year-old female ewe showing neurological signs was presented to the Veterinary Teaching Hospital, Assiut University, Egypt. Postmortem and histopathological examinations were done to investigate the pathological lessions caused by C. cerebralis.Results: Postmortem examination of the brain revealed Coenurus cyst measuring 5×3 cm associated with dilated lateral ventricle. Histopathological examination revealed extensive areas of liquefactive necrosis in the cerebrum. The necrotic area was infiltrated with lymphocytes, microglia cells and eosinophils. Internal hydrocephalus and atrophy of the ependymal cells of both lateral ventricle and choroid plexus were also seen. Conclusion: It was concluded that coenurosis might be associated with internal hydrocephalus along with some clinical and pathological findings.http://doi.org/10.5455/javar.2016.c138